2022
DOI: 10.3390/nu14245304
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Association between Adherence to the Mediterranean Diet and Health-Related Quality of Life in Spanish Children

Abstract: Health-Related Quality of Life (HRQoL) is gaining attention in children and adolescents because it is an important outcome of their health status and well-being. Therefore, it is important to identify determinants for HRQoL. Currently, there is scarce and mainly cross-sectional evidence on the relationship between adherence to the Mediterranean diet and HRQoL in children and adolescents. Therefore, the objective of the present study was to assess the prospective association between adherence to the Mediterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…This aligns with earlier observations made in Spanish adolescents, where a similar positive association between HRQoL and MedDiet adherence was documented [22,23]. Moreover, the influence of specific dietary components is emphasized, with the consumption of fruits, vegetables, and legumes emerging as notable contributors to a high perceived HRQoL, consistent with previous research highlighting their positive impact [24]. Another study found a positive association between HRQoL and the fruit and vegetable portion of the diet [50].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This aligns with earlier observations made in Spanish adolescents, where a similar positive association between HRQoL and MedDiet adherence was documented [22,23]. Moreover, the influence of specific dietary components is emphasized, with the consumption of fruits, vegetables, and legumes emerging as notable contributors to a high perceived HRQoL, consistent with previous research highlighting their positive impact [24]. Another study found a positive association between HRQoL and the fruit and vegetable portion of the diet [50].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies [6,[22][23][24][25][26][27][28] analysed the association between HRQoL and healthy lifestyle outcomes, but they were conducted using a regional sample, assessed only one outcome, were not in a national representative wide sample of the Spanish child and adolescent population, and did not assess the association between HRQoL and healthy lifestyle outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…All studies analyzed the association with linear regression and eight used adjusted models: among the latter, five found a significant positive association between DM adherence and HRQoL (with β values ranging from 0.13 to 0.26), two found a non-significant positive relationship, while one found a negative association. Recently, a positive correlation between MD adherence and HRQoL in both children and adolescents was suggested [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Establishing healthy habits from the first stages of life yields a large number of benefits. Adherence to Mediterranean diets during childhood and adolescence improves not only the child's nutritional status but also their quality of life and general well-being [27,28]. This long-term health influence has been demonstrated in several studies, reinforcing the positive influence a balanced diet has on decreasing the risk of chronic diseases such as cardiovascular disorders, diabetes, or obesity [29][30][31][32].In addition to increasing healthy feeding habits, another possibility for improving the nutritional status of toddlers and mitigating the risk of developing potential nutritional imbalances or deficiencies could come in the form of increasing adapted milk consumption [24,33].…”
Section: Discussionmentioning
confidence: 99%